Synthesis, Structural, Thermal and Biological Studies of Diaqua and Bis(triphenylphosphine) Substituted Late Transition Metal Complexes of 2-Aminopyridine - A. Ahmed, Safaa (Asian Journal of Chemistry, 2012)
Stable and neutral Co(II), Ni(II), Zn(II) and Cd(II) coordination complexes (1-8) of 2-aminopyridine were synthesized and characterized by various spectro-analytical techniques. The complexes 1-4 have octahedral geometry, with two 2-aminopyridine moieties in the same plane and two water molecules occupying the axial positions. Interesting structural variations were observed in the complexes when treated with calculated amount of triphenylphosphine (PPh3) to replace the weaker water coordination. Atomic absorption and SEM techniques were also employed to analyze the metal content and surface nature of the complexes. 31P, 13C and 1H NMR studies of PPh3 coordinated complexes 5-8 confirmed the presence of phosphorous coordination through the axial positions. Finally, all the complexes showed potential activity in antimicrobial analysis against gram positive and negative bacteria.